Phytochemical Constituents and Pharmacological Activities of Houttuynia cordata Thunb. as a Phytopharmaceutical: A Narrative Review - Asih Triastuti; Juldani Adytia; Uzulul Hikmah; Putri Ananditia (Universitas Wahid Hasyim Semarang, 2026)
Houttuynia cordata Thunb. is a promising medicinal plant recognized for its rich diversity of secondary metabolites, particularly flavonoids and essential oils, that are differentially distributed across its plant organs. This narrative review aimed to critically synthesizes the reported pharmacological activities, specific phytochemical constituents of each organ, molecular mechanisms of isolated bioactive compounds, and contributions of the metabolites produced by associated endophytic microorganisms. Relevant literature was identified through electronic databases including PubMed, Scopus, ScienceDirect, and Google Scholar using the keywords “Houttuynia cordata”, “phytochemical”, “pharmacological activity”, and “secondary metabolites”, from 2015-to 2025. A broad body of literature published was examined to map the diversity of bioactive compounds, experimental models, and mechanisms of action. The findings reveal that the leaves of H. cordata are rich in flavonoids such as quercetin and rutin, which act as potent antioxidants and immunoprotective agents. The stems and rhizomes are dominated by monoterpenes and volatile ketones exhibiting marked antimicrobial and anti‑inflammatory properties. Preclinical evidence consistently demonstrates antitumor activity via apoptosis induction, multitarget antiviral effects, antidiabetic, and antihyperlipidemic activities as well as anti‑inflammatory actions mediated through the inhibition of TNF‑α and PGE₂ pathways. Antibacterial and anticancer properties are also notably attributable to the secondary metabolites produced by the endophytic microbiota associated with this plant. The phytochemical diversity of H. cordata and its symbiotic endophytes offer promising prospects for the discovery of novel bioactive compounds from Indonesian biological resources. Collectively, H. cordata holds substantial potential as antioxidant, antimicrobial, antivirus, anticancer, antidiabetic, antihyperlipidemic, anti-inflammatory, immunomodulatory, and antiasthma, warranting further investigation as an innovative phytopharmaceutical candidate.